Unemployment, temporary work and subjective well-being Gendered effect of spousal labour market insecurity in the United Kingdom - Inanc, Hande (OECD Statistics Working Papers, 2016)
This paper investigates the extent to which unemployment and temporary work - two forms of labour market insecurity - affect different aspects of subjective well-being (i.e. life satisfaction, psychological well-being and satisfaction with partnership) among legally married and cohabiting couples in the United Kingdom. Drawing on matched data for couples from the British Household Panel Study, the paper shows that both forms of labour market insecurity, when experienced by the male partner, lower significantly the psychological well-being and life satisfaction of the female partner; women's temporary work also slightly lowers men's psychological well-being. The impact of spousal labour market insecurity depends, however, on the employment status of the individual: after controlling for financial strain, psychological well-being and life-satisfaction of both partners in a couple are hampered the most when men are economically dependent on their female partners. In the case of partnership satisfaction, results differ from the other two subjective well-being outcomes: while unemployment of the female partner is associated with higher satisfaction for men, partnership satisfaction is particularly low when both partners experience either form of labour market insecurity. These effects are robust after controlling for fixed individual characteristics that can influence both employment status and well-being outcomes